Helping Mothers Survive Bleeding after Birth Training Join project between University of Gezira, Jhpiego- affiliated with Johns Hopkins University, Sudanese American Medical Association (SAMA), Sudanese Obstetrical and Gynaecological Society - Miskeen, Elhadi Ibrahim; Khalafalla, Somia; A/Rahim, Mohamed; Gadelalla, Nahla; Mohamed, Mohamed Elsanousi; Mirghani, Omer Ahmed (Gezira Journal of Health Sciences, 2016)
Abstract: The post partum haemorrhage (PPH) Project of Sudan should consider facilitation of implementation of a more comprehensive and innovative program to address prevention, identification and management of PPH with the goal of improving the quality of care and health outcomes related to PPH. The Master Trainer Course was held at the University of Gezira (U of G) followed by Champion courses and Clinical Mentor orientation sessions in 5 hospitals (4 rural and 1 urban). There are additional 5 hospitals in Gezira state where providers have yet to receive the Champions course. The additional courses are planned in March and April of 2016. 23 Master Trainers were mentored in help mother survive (HMS). The PPH Project Director based at UofG and additional 2 more trainers were introduced to the principles of HMS training and the low dose high frequency (LDHF) approach was adopted. 155 providers participated in a bleeding after birth (BAB) Champions Course. 106 of the participants were village midwives who received selected updates around child birth to address gaps identified during the opening role play. Updates included being patient during second stage of labour, no pulling of fetus, delivering babies to mothers , abdomen/skin to skin, drying the baby immediately, changing the wet cloth and covering the baby with dry cloth while on mothers’ abdomen, not to hold babies upside down, not to separate babies from mothers after cutting the cord. No cord milking, evacuation of birth canal in the name of “cleaning” it, no routine episiotomy or pulling the placenta without counter pressure and few others. 34 providers from 5 hospitals (4 rural and 1 urban) were oriented as clinical mentors. They will conduct peer mentorship at respective hospitals as well as the downward type of mentorship to midwives at health centers and village midwives from respective community neighborhood